Preseason shoulder rotational isokinetic strength and shoulder injuries in volleyball players - Hadžic, V.; Derviševic, E.; Pori, P.; Hadžic, A.; Sattler, T. (Isokinetics and Exercise Science, 2022)
BACKGROUND: Rotator cuff weakness is considered an important risk factor for shoulder injuries in volleyball. OBJECTIVE: To evaluate association of shoulder preseason strength status with shoulder injury occurrence in subsequent season. METHODS: Volleyball players (N= 181; 99 men) from Slovenian 1st and 2nd national league volunteered to participate in this prospective cohort study. Preseason isokinetic testing of the shoulder was conducted at 60°/s in the concentric mode of contraction over a RoM of 60° with five repetitions of internal (IR) and external (ER) rotation. During the subsequent season the players reported shoulders injuries through a weekly questionnaire. RESULTS: During the season we have registered 14 (7.7%) shoulder injuries (10 in men). All injuries affected the dominant shoulder. There was significant preseason weakness of ER and lower ER/IR strength ratio in players with shoulder injury. Normal strength ratio ER/IR was a significant protective factor (Exp (B) = 0.217, 95% C.I. 0.058-0.811) for shoulder injury occurrence when controlled for sex and previous injury. CONCLUSIONS: The inclusion of systematic strengthening of the external rotators of the shoulder is necessary, especially for male volleyball players, as part of preventive measures for the prevention of shoulder injuries.